2005
DOI: 10.1097/01.prs.0000160269.73323.67
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial Morphology in Children with Complete Unilateral Cleft Lip and Palate Treated by One-Stage Simultaneous Repair

Abstract: Because both of the surgical treatment procedures give rise to similar maxillofacial development outcomes, regardless of the timing of surgery, the one-stage procedure offers several important advantages, such as less psychosocial trauma, low cost, and possibly an improvement in speech results because of less scarred palatal fields and the low rate of palatal fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…Most authors 13,[17][18][19]21 highlighted significant reduction of the upper posterior facial height (S-Pmp). The present results confirmed significant reduction of the upper posterior facial height (S-Pmp) in all groups (I p < 0.001; II p < 0.001; III p < 0.001) compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most authors 13,[17][18][19]21 highlighted significant reduction of the upper posterior facial height (S-Pmp). The present results confirmed significant reduction of the upper posterior facial height (S-Pmp) in all groups (I p < 0.001; II p < 0.001; III p < 0.001) compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6]11 Different management protocols have different impact on the development of craniofacial morphology. 4,7,8,13,15,[17][18][19]24,[27][28][29] This study has compared the craniofacial morphology of children with complete unilateral cleft lip and palate treated with three different surgical protocols, the only difference which is in the technique employed to perform hard palate closure.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the Comprehensive Rehabilitation Services in Uganda (CoRSU) hospital, very early synchronous repair of the cleft lip and palate (CLP) is considered to be a lifesaving procedure for Ugandan patients with CLP. The synchronous repair is advocated as failure to complete palatoplasty after lip repair is highly frequent in African patients with CLP due to operation costs, traveling costs, traveling distance and recovered aesthetics [13,14] - in black African societies, clefts are often associated with evil spirits, curses and punishment for ancestral wrongdoings [15]. Moreover, very early closure of the CP is advised as babies with unrepaired CP frequently lose weight in their first few months of life due to the inability to adequately breast-feed [16], resulting in a great risk for malnutrition [17].…”
Section: Introductionmentioning
confidence: 99%
“…Savaci [13] suggested that simultaneous correction of cleft lip and palate as one stage procedure offers several important advantages, such as less psychological trauma, low cost, and an improvement in speech results due to less scarred palatal fields and low rates of palatal fistula. Literature [14,15] also shows successful results with synchronous repair of bilateral cleft lip and nasal deformity.…”
Section: Discussionmentioning
confidence: 99%